Partisipasi Pedagang dalam Pengelolaan Sampah di Pasar Tradisional Banjar Adat Mambal Kajanan Badung Bali - Astuti, Widya; Adisanjaya, Ngurah; Indahsari, Ni Wayan Ayu (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Banjar Adat Mambal Kajanan Traditional Market is one of the markets that is not managed by the Regional Market Company of Badung Regency and is only managed by the Desa Adat. Traders in this market do not provide trash or plastic bags, so that garbage piles up in the corners of the kiosks and market aisles. Waste management system in this traditional market has not been in accordance with Minister of Home Affairs Regulation No. 33 of 2010 concerning Guidelines for Waste Management. This study aims to determine the relationship of knowledge, attitudes, availability of facilities and infrastructure, supervision by the market manager and policies or regulations with the participation of traders in waste management in the Traditional Market Banjar Adat Mambal Kajanan Badung Bali. This research used a cross sectional design. The sample in this study were traders at the traditional Banjar traditional market in Mambal Kajanan Badung, Bali. The results were obtained there was no relationship of knowledge with the participation of traders in waste management with a p value of 0.063 (p> 0.05). There is no relationship between attitude and trader participation in waste management with p value 0.989 (p> 0.05 There is a relationship between the availability of facilities and infrastructure, supervision and policies or regulations with the participation of traders in waste management because the p value of 0.00 (p <0.05) and each level of relationship between the availability of facilities and infrastructure, supervision and policies or regulations shows the level of very strong relationship strength. Keywords: Traditional Market, Participation, Waste Management